Case report: ALK-positive histiocytosis presented as bilateral synchronous breast masses with long-term remission on crizotinib - Zhou, Yuhang; Hurtado-Castillo, Marisabel; Pandey, Om (Frontiers in Medicine, 2023)
ALK-positive histiocytosis (APH) is a rare type of histiocytic neoplasm with characteristic ALK (Anaplastic Lymphoma Kinase) gene translocation and fusion with only 27 reported cases in the literature. In this paper, we report the first case of synchronous bilateral breasts involvement of the ALK-positive histiocytosis as the initial presentation in a 46-year-old Hispanic woman. APH was diagnosed by the confirmation of clonal histiocyte proliferation with ALK overexpression on IHC, and the presence of KIF5B-ALK gene fusion from her breast and lung biopsies. Our patient is currently in complete and long-term remission with crizotinib (an ALK inhibitor) treatment. This report expands the clinical manifestation of APH, emphasizes the importance of ALK detection in histiocytic diseases, and provides the efficacy and long-term prognosis of ALK inhibitor therapy for APH.Case reportThis case describes a 46-year-old Hispanic female with hypertension and pre-diabetes, who presented to her primary care provider with enlarging bilateral breast masses and left breast nipple ulceration in June, 2020. She also endorsed chronic neck pain with new right-sided shoulder pain. She did not have any weight loss, fever, night sweats, dyspnea, cough, hemoptysis, headache, weakness, or neurologic symptoms. She did not have any family history of neoplasm or blood disorder. Her vital signs were